2021
DOI: 10.1037/aap0000188
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Korean immigrant mothers’ parenting practices: By using the framework of bilinear acculturation.

Abstract: By using the conceptual framework of bilinear acculturation, this study examined Korean immigrant mothers' parenting practices among 389 mother-youth (adolescent children in middle or high school) dyads. We examined (a) how mothers' acculturation and enculturation were related to mainstream (i.e., authoritarian vs. authoritative styles, communication, warmth/bonding, autonomy support) versus culture specific parenting practices (i.e., interdependence, commitment to education, academic control) and (b) how pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 57 publications
1
10
0
Order By: Relevance
“…Correlations among the main study variables are presented in Table 2. Consistent with previous studies (e.g., Eisenberg et al, 2005; Yoon et al, 2021), the study variables were correlated in the expected direction (e.g., child temperamental inhibitory control was negatively correlated with child externalizing problems), which provided some evidence for the convergent validity of each measure. The attrition rate was 31% for W2 and 24% for W3 ( n = 199 at W1, n = 138 at W2, and n = 105 at W3).…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Correlations among the main study variables are presented in Table 2. Consistent with previous studies (e.g., Eisenberg et al, 2005; Yoon et al, 2021), the study variables were correlated in the expected direction (e.g., child temperamental inhibitory control was negatively correlated with child externalizing problems), which provided some evidence for the convergent validity of each measure. The attrition rate was 31% for W2 and 24% for W3 ( n = 199 at W1, n = 138 at W2, and n = 105 at W3).…”
Section: Resultssupporting
confidence: 86%
“…Indeed, Korean immigrant mothers' behavioral acculturation toward the American culture was found to be positively related to parental warmth, while their Korean cultural orientation was positively related to Korean culture-emphasized parenting (e.g., interdependence; Yoon et al, 2021). Parental warmth is therefore expected to be more strongly associated with American acculturation than with a Korean cultural orientation, perhaps because parental warmth, especially expressive forms of warmth, is more normative and encouraged in Western cultures than in Asian cultures (Cheah et al, 2015).…”
Section: Maternal Acculturationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is important to note that a recent meta-analysis concluded that authoritarian parenting is associated with negative child outcomes such as elevated internalizing and externalizing problems and poorer academic performance across different cultural and ethnic groups, including Chinese and Chinese American families (Pinquart & Kauser, 2018). Although some studies have found that authoritarian parenting may be less detrimental to child development in Asian samples (e.g., Ang, 2006;Pong et al, 2010;Yoon et al, 2021), the majority of more recent research indicates that this form of parenting is generally associated with negative child developmental outcomes in Asian American families (Kho et al, 2019;Shen et al, 2018;. Thus, it is imperative to investigate potential contributors to Chinese American mothers' engagement in authoritarian parenting and potential mediating and moderating processes in this association, which can inform prevention and intervention efforts designed to promote positive parenting in Chinese American families with immigrant backgrounds.…”
Section: Racial Discrimination and Chinese American Mothers' Authorit...mentioning
confidence: 99%